Simulation framework and development of the Future Systems Simulator - Korek, Wojciech Tomasz; Beecroft, Peter; Lone, Mudassir; Bragado Aldana, Estela; Mendez, Arthur; Enconniere, J.; Asad, Hafiz Ul; Grzedzinski, Kacper; Milidere, Murat; Whidborne, James F.; Li, Wen-Chin; Lu, Linghai; et al. (Cambridge University Press (CUP), 2024)
The Aerospace Integration Research Centre (AIRC) at Cranfield University offers industry and academia an open environment to explore the opportunities for efficient integration of aircraft systems. As a part of the centre, Cranfield University, Rolls-Royce, and DCA Design International jointly have developed the Future Systems Simulator (FSS) for the purpose of research and development in areas such as human factors in aviation, single-pilot operations, future cockpit design, aircraft electrification, and alternative control approaches. Utilising the state-of-the-art modularity principles in simulation technology, the FSS is built to simulate a diverse range of current and novel aircraft, enabling researchers and industry partners to conduct experiments rapidly and efficiently. Central to the requirement, a unique, user-experience-centred development and design process is implemented for the development of the FSS. This paper presents the development process of such a flight simulator with an innovative flight deck. Furthermore, the paper demonstrates the FSS’s capabilities through case studies. The cutting-edge versatility and flexibility of the FSS are demonstrated through the diverse example research case studies. In the final section, the authors provide guidance for the development of an engineering flight simulator based on lessons learned in this project.
Keywords: flight simulation; human-computer interaction; human factors; flight deck design; aircraft modelling; 40 Engineering; 4001 Aerospace Engineering; 4010 Engineering Practice and Education; Aerospace & Aeronautics; 35 Commerce, management, tourism and services